Why women say no to leadership positions - October, Tessie W. (Frontiers in Pediatrics, 2022)
Despite a growing trend of more women entering pediatric critical care training programs, women continue to be underrepresented in leadership positions. A 2019 report on the pediatric critical care workforce revealed that only 32% of division directors are women and 25% of Department of Pediatrics Chairs are women. Women in critical care face systemic barriers to advancement into leadership positions which often lead women to reject leadership positions despite being appropriately matched or even overqualified for the position. The obstacles can appear insurmountable, especially for women of color and mothers of young children. In this article, I share my perspective on strategies to reduce these hurdles by providing guidance on preparing for these roles, embracing and promoting women when opportunities arises and matching recruitment packages to women’s values. If the goal is to recruit and retain more women into the ranks of academic leadership, especially women of color, academia must transform current practices. An approach that aims to fully understand the leader’s motivation is a key first step. Additionally, we need to invest in women earlier in their career, reward often uncompensated work, value women at their home institution, offer salary transparency and recognize the unique challenges of leading while mothering.